Pengaruh Literasi Wakaf, Transparansi Laporan Keuangan, dan Inovasi Produk Keuangan Syariah terhadap Minat Masyarakat dalam Berwakaf Tunai di Kota Medan - Rahmah, Nuzulliah; Saparuddin; Yenni Samri Juliati Nasution (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2024)
This study aims to analyze the influence of Waqf Literacy, Financial Report Transparency, and Islamic Financial Product Innovation on the Community's Interest in Cash Waqf in Medan City. The research adopts a quantitative approach, with data collected through questionnaires from 150 respondents in specific areas of Medan City. Data analysis was conducted using multiple linear regression with the help of SPSS version 23.The results show that partially, Waqf Literacy, Financial Report Transparency, and Islamic Financial Product Innovation positively and significantly influence the community's interest in cash waqf. Simultaneously, these three variables also contribute significantly to increasing interest. These findings emphasize the importance of improving literacy, transparency, and innovation in creating a more attractive and trustworthy cash waqf ecosystem. This study contributes novelty by integrating these three variables in the context of cash waqf in Medan City.